2015
DOI: 10.3329/jesnr.v7i2.22205
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impact in Charlands in Central Area of Bangladesh: Assessing Vulnerability and Adaptation by the Farming Communities

Abstract: Bangladesh, with an area of 147 thousand km 2 and population of 149.78 million, is prone to natural hazards (PHC, 2011). The objectives of the study were to determine the climatic parameter specially temperature and rainfall pattern, assess hazard, vulnerability and adaptation to climate change. Assessment was made during April to June 2013 in char areas of Kazipur upazila under Sirajgonj district. Primary data were collected through Focus Group Discussions and direct observation of the researcher. Secondary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This paper did not follow comprehensive community survey which would have allowed researchers to get a more accurate and new types of adaptation strategies. Source: [9] This research also did not focus on the comparison of different methods using clear photographs only because of shortage of available photographs in the literature. Though these limitations, researchers tried to find out maximum numbers of flood adaptation strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper did not follow comprehensive community survey which would have allowed researchers to get a more accurate and new types of adaptation strategies. Source: [9] This research also did not focus on the comparison of different methods using clear photographs only because of shortage of available photographs in the literature. Though these limitations, researchers tried to find out maximum numbers of flood adaptation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Hossain and Rahman [8] studied about the adaptation techniques of char dwellers in the five district of Bangladesh including Rangpur, Kurigram, Gaibandha, Dinajpur, and Lalmonirhat. However, Roy et al [9] discussed about the adaptation techniques of farming communities in char lands of Sirajganj in central Bangladesh. Another study had found the adaptation techniques including water supply, sanitation, and health of flood affected [10].…”
Section: Introductionmentioning
confidence: 99%